Nazis in pre-war London 1930 - 1939 : the fate and role of German party members and British sympathizers - Barnes, James J. 1931- (Sussex Academic Press, 2005)
A Nazi journalist comes to London -- Founding the London Ortsgruppe -- Otto Bene, Ortsgruppenleiter, 1932-1935 -- Establishing a Nazi brown house -- The expulsion of Hans Wilhelm Thost -- Appointment of a Nazi consul-general -- The Nazi takeover of the German news agencies -- Party and SS members in the German embassy -- Bonhoeffer and the struggle for church autonomy -- Nazi infiltration of business and labor -- Mosley's British Union of Fascists -- Nazi influence over the British Legion -- Otto Karlowa and the Landesgruppe Gross Britannien -- The government's dilemma: whether to outlaw foreign organizations -- German journalists -- Nazi intimidation leads to deportations -- The question of espionage